Highly Permeable DNA Supramolecular Hydrogel Promotes Neurogenesis and Functional Recovery after Completely Transected Spinal Cord Injury. Issue 35 (23rd July 2021) - Yuan, Taoyang; Shao, Yu; Zhou, Xu; Liu, Qian; Zhu, Zhichao; Zhou, Bini; Dong, Yuanchen; Stephanopoulos, Nicholas; Gui, Songbai; Yan, Hao; Liu, Dongsheng
Abstract: Regeneration after severe spinal cord injury cannot occur naturally in mammals. Transplanting stem cells to the injury site is a highly promising method, but it faces many challenges because it relies heavily on the microenvironment provided by both the lesion site and delivery material. Although mechanical properties, biocompatibility, and biodegradability of delivery materials have been extensively explored, their permeability has rarely been recognized. Here, a DNA hydrogel is designed with extremely high permeability to repair a 2 mm spinal cord gap in Sprague–Dawley rats. The rats recover basic hindlimb function with detectable motor‐evoked potentials, and a renascent neural network is formed via the proliferation and differentiation of both implanted and endogenous stem cells. The signal at the lesion area is conveyed by, on average, 15 newly formed synapses. This hydrogel system offers great potential in clinical trials. Further, it should be easily adaptable to other tissue regeneration applications. Abstract : A DNA supramolecular hydrogel carrying neural stem cells (NSCs) is applied to repair spinal cord injury. A renascent neural network is formed at the lesion site via the proliferation and differentiation of NSCs. Due to the newly formed synapses at the lesion area, rats recover basic hindlimb function with detectable motor‐evoked potentials.